Internal marketing in hotel chains : a case study of Elite Stadshotell Luleå - Rydberg, Isabella; Lyttinen, JP (2005)
When different external factors affect organizations internally, it is important to have a good internal marketing, especially in service companies, where the employee turnover usually is higher than in other businesses, and where companies are dependent on the encounters and relations between customer and employee. In our case, where we focused on a hotel chain, managers must ensure that all employees are aware of what the company stands for, are motivated and that everyone has all the information they need to fulfill their tasks. The purpose of this thesis is to increase the understanding of how hotel chains carry out their internal marketing: how internal marketing in hotel chains can be described and how internal marketing is used to motivate employees. A qualitative case study of Elite Stadshotell Luleå was carried out. The results show that internal marketing is used, mainly in order, to create a united front towards the customer, and as a motivator through different activities. Nevertheless, conclusions can be drawn that the communication process is not as effective as they would like it to be, and that the focus lies more on external than internal issues. Validerat; 20101217 (root)